Perancangan Lemari Pendingin Sayuran dengan Media Es Batu dan Kontrol Kelembaban - Abdul Muin; Dewi Rawani; Rita Maria Veranika; Imam Akbar (Universitas Sriwijaya, 2023)
This study aims to design a vegetable refrigerator that uses ice cubes and humidity control. This refrigerator is designed to preserve vegetables that are not sold out in village stalls. This study uses an experimental method by testing three types of vegetables, namely spinach, tomatoes, and potatoes. The test was carried out for 10 hours by comparing the condition of the vegetables stored inside and outside the refrigerator. The results showed that the refrigerator could lower the room temperature to 19.7 °C and 21.5 °C for the three types of vegetables. The cooling rate that occurred for spinach was 3.342 °C/hour, for tomatoes 2.54 °C/hour, and for potatoes 2.285 °C/hour. The product weight loss that occurred was greatest in spinach, which was 31 grams, while the smallest was in potatoes, which was 2 grams. The relative humidity achieved ranged from 61% to 72%. In terms of freshness and texture, spinach showed the most significant change, while tomatoes and potatoes still maintained their quality. This study proves that vegetable refrigerators with ice cubes and humidity control can be used as an alternative appropriate technology for vegetable preservation in village stalls.